2017
DOI: 10.1016/j.diabres.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

A successful transition to sulfonylurea treatment in male infant with neonatal diabetes caused by the novel abcc8 gene mutation and three years follow-up

Abstract: Neonatal diabetes mellitus is a rare monogenic disease with incidence of 1/90,000 newborns. A case of two months aged male infant with life threatening diabetic ketoacidosis is presented with novel ABCC8 gene mutation (p.F577L), successful transition from insulin to sulfonylurea and follow-up of three years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…As the widely used drugs for the treatment of patients with type 2 diabetes, SUs could bind specifically to the SUR1 subunit, then closing the K ATP channel via an ATP-independent mechanism and therefore increasing the insulin secretion of β cells [ 52 ]. Several studies observed that patients with NDM were transferred to SUs successfully after molecular genetic diagnosis of ABCC8 variants [ 53 , 54 ]. Up to 90–95% of patients with NDM due to using ABCC8 and KCNJ11 variants are able to be taken off of insulin therapy after initiation of SUs therapy [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the widely used drugs for the treatment of patients with type 2 diabetes, SUs could bind specifically to the SUR1 subunit, then closing the K ATP channel via an ATP-independent mechanism and therefore increasing the insulin secretion of β cells [ 52 ]. Several studies observed that patients with NDM were transferred to SUs successfully after molecular genetic diagnosis of ABCC8 variants [ 53 , 54 ]. Up to 90–95% of patients with NDM due to using ABCC8 and KCNJ11 variants are able to be taken off of insulin therapy after initiation of SUs therapy [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,61 Several approaches have been utilized for transition from insulin to SU. 2,44,50,[62][63][64] Patients can be on multiple daily insulin injections or on CSII prior to transition to SU. Point of care blood glucose should be checked before meals and at bedtime daily during the transition phase.…”
Section: Sulfonylurea Therapymentioning
confidence: 99%
“…NDM is defined as the occurrence of severe hyperglycemia starting from the first month of life in the neonates ( Sethi et al., 2020 ). The global incidence of NDM ranges between 1:90,000–1:160,000 in live births ( Katanic et al., 2017 ; Rubio-Cabezas and Ellard, 2013 ; Dahl and Kumar, 2020 ). NDM was first noticed as the beginning of the 9 th century, but diabetes in children was not confirmed as T1DM/insulin dependent diabetes and ketotic due to the absence of clinical features ( Aguilar-Bryan and Bryan, 2008 ).…”
Section: Introductionmentioning
confidence: 99%